A LEGAL ANALYSIS OF THE CILOK KAYI TRADITION IN MUKOMUKO - Nurjannah, Revalysa Zovi; Jufrizal, Jufrizal (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This article discusses the ‘Urf Review of Cilok Kayi in Mukomuko Regency, Bengkulu This type of research uses a descriptive method with a qualitative approach so that it can find out directly the implementation of the tradition. While research data collection is carried out by means of observation, interviews and documentation obtained directly from sources related to the research, in this case the informants consist of religious leaders, traditional leaders, and some of the Mukomuko community. The research suggests that Cilok Kayi, a community tradition related to food or local customs, may not be considered ‘Urf fasid in Islamic law. However, if customary sanctions are imposed for non-observance, the tradition may be considered ‘Urf fasid, potentially violating the principles of freedom and justice. The study emphasizes the importance of considering the social, cultural, and religious context when assessing the legal status of a tradition in Islam, particularly in the case of ‘Urf fasid.